A composite generator film impregnated with cellulose nanocrystals for enhanced triboelectric performance. Issue 4 (16th January 2017) - Peng, Jun; Zhang, Huilong; Zheng, Qifeng; Clemons, Craig M.; Sabo, Ronald C.; Gong, Shaoqin; Ma, Zhenqiang; Turng, Lih-Sheng
Abstract : A novel composite structured film impregnated with oriented cellulose nanocrystal flakes (CNCFs) as an effective dielectric could enhance generator performance and energy conversion efficiency. Abstract : A novel polydimethylsiloxane (PDMS)/cellulose nanocrystal flake (CNCF) composite triboelectric nanogenerator (CTG) using CNCFs as effective dielectrics exhibited a 10-times-enhanced triboelectric performance compared with its pure PDMS counterpart. Positive charges generated on the surface of the CNCFs during cyclic compression boosted electron transfer and induced extra charges. The CTG exhibited an instantaneous output power (density) of 1.65 mW (0.76 mW cm −2 ) under continuous operation.